Efeito antibacteriano do óleo essencial de Origanum majorana e de compostos isolados na forma pura e nano encapsulada contra à Aeromonas hydrophila em Rhamdia quelen - Cunha, Jessyka Arruda da (2018)
The first article aimed to provide a review of the in vivo and in vitro studies that addressed the use of essential oils (EOs) and their main compounds as antimicrobial agents in fish, to identify the best EOs and compounds, besides investigating feasibility of application and suggest future studies. To date, studies have suggested that the use of EOs in the prevention and/or treatment of infectious diseases in fish may be a promising strategy to reduce the use of conventional antibiotics in aquaculture since several EOs reduce or avoid the effects of bacterial infections in fish. The use of EOs through nanotechnology distribution systems, especially in dietary supplementation experiments, is promising. This form of application of the EOs allows their potentialization, aiming at the desired effect of the EOs and also allows the protection of the active constituents of the EOs. The second article evaluated the antibacterial activity of the EO of Origanum majorana (EOM) and nanocapsules of this oil (NOM) in Rhamdia quelen infected with Aeromonas hydrophila, in addition to investigating the possible effects on metabolic parameters of the animals. The treatment was performed through daily baths of 1h for 5 consecutive days. All treatments improved the survival rate of infected fish, but we suggest treatment of A. hydrophila infections by daily baths with 20 μL L-1 EOM or 5 μL L-1 NOM for five consecutive days. The third article aimed to evaluate the resistance of R. quelen to A. hydrophila infection after treatment with pure and nanoencapsulated forms of terpinen-4-ol, thymol, or carvacrol and the effects of these treatments on the metabolic responses of fish. After inoculation with A. hydrophila, fish were treated with 30 min daily baths for six consecutive days. Fish treated with the nanoencapsulated form of the compounds had a high survival rate, similar to saline and negative control groups. The nanoencapsulated forms of carvacrol, thymol, and terpinen-4-ol improved the survival of silver catfish infected by A. hydrophila. However, muscular and hepatic glucose and lactate levels are not indicated as biomarkers, since they did not present a correlation between the metabolic state of the fish and the bacterial infection.